Review of sweet and sour cherry incompatibility - Békefi, Zs. (International Journal of Horticultural Science, 2006)
Cherry incompatibility has widely been studied from the beginning of the twentieth century. As a consequence of the valuable results cherry has become a model for incompatibility research of other plant species. This study provides a detailed information about incompatibility of sweet and sour cherry based on several Hungarian and international literature sources from the last 100 years. The study gave details about the traditional and molecular base of incompatibility of sweet and sour cherry.